2016
DOI: 10.1186/s13046-015-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

Gab2 facilitates epithelial-to-mesenchymal transition via the MEK/ERK/MMP signaling in colorectal cancer

Abstract: BackgroundGrb2-associated binder 2 (Gab2), a scaffolding adaptor protein, has recently been implicated in cancer progression. However, the role of Gab2 in the progression and metastasis of colorectal cancer (CRC) remains unclear.MethodsGab2 expression was assessed in CRC patient specimens as well as in CRC cell lines. Recombinant lentivirus vector containing Gab2 gene and its small interfering RNAs were constructed and introduced into CRC cells. Cell migration and invasion ability were evaluated by transwell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…Bewilderingly, the ERK, but not PI3K and p38 signaling pathways may be crucially involved in the invasion, proliferation and EMT induced by HspB5 over-expression in Lovo Cells. One plausible explanation is that the functions of PI3K/Akt, ERK and Raf/MAPK in EMT might depend on the different cell types[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bewilderingly, the ERK, but not PI3K and p38 signaling pathways may be crucially involved in the invasion, proliferation and EMT induced by HspB5 over-expression in Lovo Cells. One plausible explanation is that the functions of PI3K/Akt, ERK and Raf/MAPK in EMT might depend on the different cell types[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Invasion assays were performed as reported [ 20 ]. Transwell invasion assays were performed in Corning Matrigel invasion chamber containing an 8 μm pore-size polycarbonate membrane with a uniform layer of BD Matrigel basement membrane matrix (BD Biosciences, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical assay for paraffin-embedded tissues were performed as reported [ 19 , 20 ]. The evaluation principle was quantified based on the immunoreactive score (IRS), which was calculated as a product of staining intensity (SI) and percentage of positive cells (PP).…”
Section: Methodsmentioning
confidence: 99%
“…When treated with small chemical inhibitors against key factors of pathways (U0126 and LY294002), we found that MMP13 expression was inhibited by the blockaded of ERK signaling in tumor cells. Recently, ERK/MMP pathway was shown to facilitate epithelial-to-mesenchymal transition in colorectal cancer [29]. The study by Liang et al [30] indicated that interleukin-1-induced MMP9 expression required the activation of ERK signaling.…”
Section: Discussionmentioning
confidence: 99%